DEVELOPMENT OF FORECASTING SCENARIOS OF THE ELECTRICITY CONSUMPTION IN UKRAINE BY USING THE GROUP METHOD OF DATA HANDLING - Stepashko, Volodymyr; Trachuk, Andrii (Технічні науки та технології, 2021)
Considered problem issues of electricity consumption in Ukraine. The dynamics of energy consumption and the proposed guidelines gait efficient use of electricity. Researched and projected scenarios projected electricity consumption in general throughout Ukraine. The basic foundation of the formation of the Ukraine grid construction is forecasting scenarios for different types of energy and the various criteria for effective use of energy resources. The problem of efficient use of energy resources raises crucial for sustainable economic development against the backdrop of energy saving national economy depends on energy imports, on the one hand, and rising prices for these resources. The solution to this problem is not only with ensuring energy security, but also with the level of development of regions and the quality of life of its population.